No abismo de si: a descentralização do sujeito em O falso mentiroso: memórias, de Silviano Santiago - Nogueira, Gabriel Jodas (2017)
O Falso Mentiroso: memórias (2004) is stablished through the confusion between referential reality and fictional narrative. In addition to suggesting a novelized autobiography of Samuel Carneiro de Souza Aguiar, it goes beyond in the theoretical content related to aesthetics, identity and the write of self. Such themes, recurring in the epistemological setting of postmodernity, are carried by the fiction of a writer acclaimed for the vast theoretical work in the field of literary studies. Therefore, this research will investigate Santiago's novel based on the theory brought by the Canadian author Linda Hutcheon in her book A poetics of Postmodernism . The fiction will be analysed regarding its resemblance to a category of postmodern texts called Historiographic Metafictions, for there is an eruption of historical events and data that are redesigned by the narrator's ironic discourse. Samuel tells his frustrations regarding his parentage, since there are many versions of how he came to his fake parents' house. According to the fifth and last possibility, the narrator was born in Formiga, in the state of Minas Gerais, in the year 1936. Such information of Silviano's empirical reality plays with the reader, who keeps looking for the author in the character created by him, like a bloodhound. In the shuffling of categories related to reality and fiction, the writer looks at the identitary process of the conflicting subject in postmodernity. The identitary process, besides demonstrating the solidity of our identity, brings up its ephemerality and the relentless strikes against the subjectivity. That taken into consideration, this work presents, in the first chapter, a new approach to Silviano's narrators. This approach is called Identitary Metafiction, which aims not only to name the main characteristics of his writings, but also to give them a whole new meaning.